Contribution of GnIH Research to the Progress of Reproductive Neuroendocrinology - Tsutsui, Kazuyoshi; Ubuka, Takayoshi; Son, You Lee; Bentley, George E.; Kriegsfeld, Lance J. (Frontiers in Endocrinology, 2015)
Since the discovery of gonadotropin-releasing hormone (GnRH) in mammals at the beginning of the 1970’s, it was generally accepted that GnRH is the only hypothalamic neuropeptide regulating gonadotropin release in mammals and other vertebrates. In 2000, however, gonadotropin-inhibitory hormone (GnIH), a novel hypothalamic neuropeptide that actively inhibits gonadotropin release, was discovered in quail. Numerous studies over the past decade and a half have demonstrated that GnIH serves as a key player regulating reproduction across vertebrates, acting on the brain and pituitary to modulate reproductive physiology and behavior. In the latter case, recent evidence indicates that GnIH can regulate reproductive behavior through changes in neurosteroid, such as neuroestrogen, biosynthesis in the brain. This review summarizes the discovery of GnIH and the contributions to GnIH research focused on its mode of action, regulation of biosynthesis, and how these findings advance our understanding of reproductive neuroendocrinology.